Preparation method of sandwich structure foamy copper with metallurgical bonding interface

By using an integrated molding process that combines the pore-forming agent method and the direct powder sintering method in the preparation process of copper foam, a sandwich structure of copper foam is formed, which solves the challenge of balancing porosity and strength of existing metal foams and achieves The effect of high porosity and high strength coexisting.

CN119328144APending Publication Date: 2025-01-21JIANGXI UNIV OF SCI & TECH
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411719701.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing foam metals have challenges in improving porosity and strength, especially the metallurgical bonding interface is mainly formed by one-way diffusion, and there is a lack of bidirectional diffusion research.

Method used

An integrated molding process that combines the pore-forming agent method and the direct powder sintering method is used to form a sandwich structure of copper foam through layer-by-layer pressing and sintering, achieving bidirectional diffusion between the copper foam core layer and the metal panel to form a metallurgical bonding interface.

Benefits of technology

The porosity and mechanical properties of copper foam are significantly improved, forming a sandwich structure copper foam with higher interface bonding strength and better durability, which is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119328144A_ABST
    Figure CN119328144A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of sandwich-structure foamy copper with a metallurgical bonding interface. The preparation method comprises the steps that (1) copper powder is poured into a mold to be pressed and formed, and a first surface layer is obtained; (2) pouring a mixture of copper powder and a pore-forming agent into the pressed blank in the step (1), and pressing and forming to obtain a core layer; (3) copper powder is poured into the pressed blank obtained in the step (2) to be pressed and formed to obtain a second surface layer, and meanwhile a pressed blank of a sandwich structure is formed; and (4) putting the sandwich structure pressed blank into a vacuum tube furnace, slowly heating at low temperature to remove the core layer pore-forming agent, then heating to high temperature to sinter, and cooling to obtain the sandwich structure foamy copper. A metallurgical bonding interface is formed through bidirectional diffusion between copper powder particles in a contact area between the foamy copper core layer and the surface layer. The interface bonding strength is higher, the durability is better, the comprehensive mechanical property of the whole sandwich structure foamy copper can be remarkably improved, the service life of the whole sandwich structure foamy copper can be remarkably prolonged, and the preparation process is relatively simple, easy to control and suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to a method for preparing a layered structure material, in particular to a method for preparing sandwich structure foam copper by using powder metallurgy technology. Background Art

[0002] The development of new lightweight and high-strength materials is a common and urgent need in key areas such as aerospace, automobiles, and consumer electronics. As an excellent lightweight porous metal material, foam metal has strong requirements for its high porosity and high strength. However, the high porosity and high strength of foam metals are often not achieved at the same time. The foam metal prepared by electrodeposition shows ultra-high porosity due to the use of high-porosity polyurethane foam plastic as a precursor, but its mechanical properties are greatly reduced due to the hollow structure of the skeleton. Although melt foaming and powder metallurgy provide a promising strategy for preparing solid skeleton foam metals, it is still a huge challenge to prepare foam metals that have both high porosity and high strength.

[0003] In recent years, the academic community has gradually turned its attention to making metal foam into a sandwich structure to solve the problem of low mechanical strength faced by single metal foam. As the name implies, a metal foam sandwich is a layered composite material consisting of two layers of metal panels and a core layer of metal foam. On the basis of maintaining the high porosity of the middle core layer of metal foam, it relies on two layers of metal panels to withstand higher mechanical loads, which not only further improves the performance of metal foam but also expands the application range of metal foam. Therefore, the sandwich structure is expected to become a highly competitive candidate method for improving the strength of metal foam. However, so far, the positive role of the sandwich structure in improving the strength of metal foam is basically concentrated on aluminum foam. According to relevant literature reports published in the past five years, the preparation methods of aluminum foam sandwiches mainly include melt foaming, welding, powder metallurgy and bonding. The first three methods can form a metallurgical bonding interface between the aluminum foam core and the metal panel. Compared with the bonding interface, the metallurgical bonding interface has the advantages of high interface bonding strength and good weather resistance, which greatly improves the mechanical properties and service life of the metal foam sandwich. However, the existing metallurgical bonding interface is formed by unidirectional diffusion from the foam core layer to the metal face plate, but there is a serious lack of literature research on the foam-metal sandwich in which the metallurgical bonding interface is formed by bidirectional diffusion between the foam core layer and the metal face plate.

[0004] Copper is an important nonferrous metal, known for its good electrical and thermal conductivity. Copper foam is a copper-based foam metal, which shows attractive application prospects in electrode current collectors, catalyst carriers, phase change material carriers, etc. In this study, we used an integrated molding process combining the pore-forming agent removal method with the powder direct sintering method to prepare a sintered copper plate-foam copper-sintered copper plate foam copper sandwich. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a sandwich structure copper foam with a metallurgical bonding interface in view of the above-mentioned defects. The method studies the process, interface bonding state and core layer foam structure of the prepared sandwich structure copper foam, and can better improve the porosity and mechanical properties of the copper foam.

[0006] The purpose of the present invention is achieved through the following technical solutions.

[0007] (1) Irregularly shaped copper powder with a purity of 99.9% and a size of ≤ 50 μm and a particle size of 40-80 mesh needle-shaped urea were selected as the pore-forming agent. According to the density (copper: 8.96 g / cm 3 , urea: 1.335 g / cm 3 ), taking a square mold with a side length of 20 mm and a height of 10-20 mm as the benchmark, and the volume fraction of the core layer pore former as 90%, calculate the mass of copper powder and urea in each layer;

[0008] (2) Pour the weighed bottom layer of dense copper powder into a square mold with an inner side length of 20 mm and maintain it at a pressure of 150-250 MPa for 20-40 seconds;

[0009] (3) Put the weighed core copper powder and urea into a beaker, stir evenly on a magnetic stirrer, pour into a mold with a bottom layer and keep it at a pressure of 150-250 MPa for 20-40 seconds;

[0010] (4) pouring the weighed surface layer dense copper powder into a mold with a bottom layer and a core layer and maintaining it at a pressure of 150-250 MPa for 20-40 seconds, and demolding to obtain a green compact of a sandwich structure foam copper sample;

[0011] (5) placing the sandwich structure copper foam green compact obtained by pressing in a square firing boat on a support frame containing a layer of 16-20 mesh fine wire mesh, and sending it into a vacuum tube furnace and heating it to 380-420 °C within 200-400 min;

[0012] (6) The temperature is then raised to 800-850°C at a rate of 5-10°C / min and kept at that temperature for 1-2 hours. The furnace is then cooled to room temperature to obtain a sandwich structure copper foam with a metallurgical bonding interface.

[0013] The beneficial effects of the present invention are as follows: the present invention prepares a copper foam with high porosity by adopting an integrated molding process combining a pore-forming agent removal method with a powder direct sintering method, and forms a sandwich structure by adding sintered copper plates on both sides of the copper foam, thereby achieving high porosity and high strength. Different from the traditional gluing method, the present invention forms a metallurgical bonding interface through bidirectional diffusion between the copper foam core layer and the metal panel. This interface has higher bonding strength and better durability, and can significantly improve the comprehensive mechanical properties and service life of the entire sandwich structure copper foam. Compared with other complex preparation methods (such as melt foaming method), the process flow proposed by the present invention is relatively simple, easy to control, and suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 The present invention is a process flow chart for preparing a sandwich structure copper foam having a metallurgical bonding interface.

[0015] Figure 2 The structural and microstructural diagrams of the specimen with a core-face height ratio of 4:1 and a height of 12 mm.

[0016] Figure 3 The structural and microstructural diagrams of the specimen with a core-face height ratio of 8:1 and a height of 10 mm.

[0017] Figure 4 The structural and microstructural diagrams of the specimen with a core-face height ratio of 10:1 and a height of 12 mm. DETAILED DESCRIPTION

[0018] Embodiment 1:

[0019] A method for preparing a sandwich structure copper foam with a metallurgical bonding interface core-to-face height ratio of 4:1 and a height of 12 mm, comprising the following steps:

[0020] (1) The volume fraction of the core pore-forming agent is set to 90%. The total volume of copper powder and urea is determined based on a square cylinder with a length of 20 mm and a height of 12 mm.

[0021] (2) Based on density (copper: 8.96 g / cm 3 , urea: 1.335 g / cm 3 ), the mass of the surface and bottom copper powders is 7.16 g, the mass of the core copper powder is 2.87 g, and the mass of the core urea is 3.84 g.

[0022] (3) Pour 7.16 g of copper powder into a square steel mold with an inner side length of 20 mm and press it axially at a pressure of 150-250 MPa for 20-40 s to form a sandwich bottom layer structure.

[0023] (4) Place 2.87 g of copper powder and 3.84 g of urea in a beaker, stir evenly on a magnetic stirrer, pour into a mold with a bottom layer and maintain at a pressure of 150-250 MPa for 20-40 seconds.

[0024] (5) Pour 7.16 g of the surface copper powder into a mold with a base layer and a core layer and maintain it at a pressure of 150-250 MPa for 20-40 seconds. De-mold to obtain a green compact of a sandwich structure copper foam sample.

[0025] (6) The green compact obtained by pressing is then placed in a square firing boat on a support frame containing a layer of 18-mesh fine wire mesh, and is sent into a vacuum tube furnace and heated to 380-420°C within 200-400 min to ensure that the urea is completely volatilized.

[0026] (7) Then, the temperature is raised to 780-850°C at a rate of 8-10°C / min and kept at this temperature for 1-2 h to allow the copper in the matrix to be fully sintered. The furnace is then cooled to room temperature.

[0027] (8) After cooling to room temperature, take out the copper foam and obtain a sandwich structure with a metallurgical bonding interface with a core-to-face height ratio of 4:1 and a height of 12 mm. The structure is as shown in the attached figure. Figure 2 shown.

[0028] Embodiment 2:

[0029] A method for preparing a sandwich structure copper foam with a metallurgical bonding interface core-to-face height ratio of 8:1 and a height of 10 mm, comprising the following steps:

[0030] (1) The volume fraction of the core pore-forming agent is set to 90%. The total volume of copper powder and urea is determined based on a square cylinder with a length of 20 mm and a height of 12 mm.

[0031] (2) Based on density (copper: 8.96 g / cm 3 , urea: 1.335 g / cm 3 ), the mass of the surface and bottom copper powders is 3.58 g, the mass of the core copper powder is 2.87 g, and the mass of the core urea is 3.84 g.

[0032] (3) Pour 3.58 g of copper powder into a square steel mold with an inner side length of 20 mm and press it axially at a pressure of 150-250 MPa for 20-40 s to form a sandwich bottom layer structure.

[0033] (4) Place 2.87 g of copper powder and 3.84 g of urea in a beaker, stir evenly on a magnetic stirrer, pour into a mold with a bottom layer and maintain at a pressure of 150-250 MPa for 20-40 seconds.

[0034] (5) Pour 3.58 g of the surface copper powder into a mold with a base layer and a core layer and maintain it at a pressure of 150-250 MPa for 20-40 seconds. De-mold to obtain a green compact of a sandwich structure copper foam sample.

[0035] (6) The green compact obtained by pressing is then placed in a square firing boat on a support frame containing a layer of 18-mesh fine wire mesh, and is sent into a vacuum tube furnace and heated to 380-420°C within 200-400 min to ensure that the urea is completely volatilized.

[0036] (7) Then, the temperature is raised to 780-850°C at a rate of 8-10°C / min and kept at this temperature for 1-2 h to allow the copper in the matrix to be fully sintered. The furnace is then cooled to room temperature.

[0037] (8) After cooling to room temperature, take out the copper foam and obtain a sandwich structure with a metallurgical bonding interface with a core-to-face height ratio of 8:1 and a height of 10 mm. The structure is as shown in the attached figure. Figure 3 shown.

[0038] Embodiment 3:

[0039] A method for preparing a sandwich structure copper foam with a metallurgical bonding interface core-to-face height ratio of 10:1 and a height of 12 mm, comprising the following steps:

[0040] (1) The volume fraction of the core pore-forming agent is set to 90%. The total volume of copper powder and urea is determined based on a square cylinder with a length of 20 mm and a height of 12 mm.

[0041] (2) Based on density (copper: 8.96 g / cm 3 , urea: 1.335 g / cm 3 ), the mass of the surface and bottom copper powders is 3.58 g, the mass of the core copper powder is 3.58 g, and the mass of the core urea is 4.81 g.

[0042] (3) Pour 3.58 g of copper powder into a square steel mold with an inner side length of 20 mm and press it axially at a pressure of 150-250 MPa for 20-40 s to form a sandwich bottom layer structure.

[0043] (4) Place 3.58 g of copper powder and 4.81 g of urea in a beaker, stir evenly on a magnetic stirrer, pour into a mold with a bottom layer and maintain at a pressure of 150-250 MPa for 20-40 seconds.

[0044] (5) Pour 3.58 g of the surface copper powder into a mold with a base layer and a core layer and maintain it at a pressure of 150-250 MPa for 20-40 seconds. De-mold to obtain a green compact of a sandwich structure copper foam sample.

[0045] (6) The green compact obtained by pressing is then placed in a square firing boat on a support frame containing a layer of 18-mesh fine wire mesh, and is sent into a vacuum tube furnace and heated to 380-420°C within 200-400 min to ensure that the urea is completely volatilized.

[0046] (7) Then, the temperature is raised to 780-850°C at a rate of 8-10°C / min and kept at this temperature for 1-2 h to allow the copper in the matrix to be fully sintered. The furnace is then cooled to room temperature.

[0047] (8) After cooling to room temperature, take out the copper foam and obtain a sandwich structure with a metallurgical bonding interface core-to-face height ratio of 10:1 and a height of 12 mm. The structure is as shown in the attached figure. Figure 4 shown.

[0048] In summary, the present invention studies a method for preparing sandwich structure copper foam using powder metallurgy technology. The surface layer of the sandwich structure material is composed of a sintered copper plate and the core layer is composed of a high-porosity copper foam. The core layer and the surface layer are pressed and formed by a layer-by-layer pressing method, and the volume fraction of the pore-forming agent in the core layer is as high as 90%. The pressing and sintering performed allow the copper powder particles in the contact area of ​​the core layer and the surface layer to form a metallurgical bond.

[0049] The preparation method and implementation examples described in the present invention are intended to demonstrate the implementation method thereof and do not limit the scope of application of the present invention. Any appropriate adjustments and improvements made on this basis, as long as they do not deviate from the core idea and technical solution of the present invention, are within the scope of protection of the present invention.

Claims

1. A method for preparing a copper foam having a metallurgical bonding interface sandwich structure, characterized in that: The following steps are included in sequence: (1) Irregularly shaped copper powder with a purity of 99.9% and a size of ≤ 50 μm and a particle size of 40-80 mesh needle-shaped urea were selected as the pore-forming agent. According to the density (copper: 8.96 g / cm 3 , urea: 1.335 g / cm 3 ), taking a square mold with a side length of 20 mm and a height of 10-20 mm as the benchmark, and the volume fraction of the core layer pore former as 90%, calculate the mass of copper powder and urea in each layer; (2) Pour the weighed bottom layer of dense copper powder into a square mold with an inner side length of 20 mm and maintain it at a pressure of 150-250 MPa for 20-40 seconds; (3) Put the weighed core copper powder and urea into a beaker, stir evenly on a magnetic stirrer, pour into a mold with a bottom layer and keep it at a pressure of 150-250 MPa for 20-40 seconds; (4) pouring the weighed surface layer dense copper powder into a mold with a bottom layer and a core layer and maintaining it at a pressure of 150-250 MPa for 20-40 seconds, and demolding to obtain a green compact of a sandwich structure foam copper sample; (5) placing the sandwich structure copper foam green compact obtained by pressing in a square firing boat on a support frame containing a layer of 16-20 mesh fine wire mesh, and sending it into a vacuum tube furnace and heating it to 380-420 °C within 200-400 min; (6) The temperature is then raised to 800-850°C at a rate of 5-10°C / min and kept at that temperature for 1-2 hours. The furnace is then cooled to room temperature to obtain a sandwich structure copper foam with a metallurgical bonding interface.

2. The method for preparing ultra-high porosity porous copper according to claim 1, characterized in that: The thickness ratio of the core layer to the surface layer of the sandwich structure copper foam is 4:1-10:

1.

3. The method for preparing a copper foam having a sandwich structure with a metallurgical bonding interface according to claim 1, characterized in that: The sandwich structure copper foam is integrally sintered by a mold pressing method.

4. A method for preparing a copper foam having a metallurgical bonding interface sandwich structure according to claim 1, characterized in that: The metallurgical bonding interface between the sandwich structure foam copper core layer and the surface layer is formed by bidirectional diffusion sintering between copper powder particles in the interface contact areas of the two layers.

Citation Information

Patent Citations

  • Method for producing foamed-aluminum sandwich panel by powder forming

    CN106735245A

  • Nano foamed aluminum composite sandwich panel with gradient interface and preparation method thereof

    CN106984818A

  • Method for preparing closed-cell foam copper-based material with powder metallurgic method

    CN107321981A

  • Composite material with lightweight sandwich structure and preparation method of composite material

    CN110238403A

  • ABA type sandwich composite material and preparation method thereof

    CN111516314A